González Gutiérrez, Patricia. ¿Existieron las romanas?. Madrid: Akal, 2024, 185 pp. [ISBN: 978-84-460-5608-9] - Lucas, Tamargo (Studia Historica. Historia Antigua, 2025)
Reseña del libro de Patricia González "¿Existieron las romanas?"